EDCs DataBank: 3D-Structure database of endocrine disrupting chemicals. (2nd January 2015) - Montes-Grajales, Diana; Olivero-Verbel, Jesus
Graphical abstract: Highlights: EDCs DataBank is the unique database with three-dimensional structures of EDCs for virtual screening. It is suitable for virtual screening and other computational approaches because the molecular structures are available in several formats. EDCs DataBank is a valuable repository to study molecular basis of the interaction of these molecules with macromolecules involved in several pathologies. This database provides information helpful for research, academia and general population. Abstract: Endocrine disrupting chemicals (EDCs) are a group of compounds that affect the endocrine system, frequently found in everyday products and epidemiologically associated with several diseases. The purpose of this work was to develop EDCs DataBank, the only database of EDCs with three-dimensional structures. This database was built on MySQL using the EU list of potential endocrine disruptors and TEDX list. It contains the three-dimensional structures available on PubChem, as well as a wide variety of information from different databases and text mining tools, useful for almost any kind of research regarding EDCs. The web platform was developed employing HTML, CSS and PHP languages, with dynamic contents in a graphic environment, facilitating information analysis. Currently EDCs DataBank has 615 molecules, including pesticides, natural and industrial products, cosmetics, drugs and food additives, among other low molecular weight xenobiotics. Therefore, this database can be used to study the toxicological effects of these molecules, or to develop pharmaceuticals targeting hormone receptors, through docking studies, high-throughput virtual screening and ligand-protein interaction analysis. EDCs DataBank is totally user-friendly and the 3D-structures of the molecules can be downloaded in several formats. This database is freely available athttp://edcs.unicartagena.edu.co .